A NEW VALIDATED SIMULTANEOUS REVERSED-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY ASSAY METHOD FOR ESTIMATION OF TWO FLAVONES (BAICALEIN AND CHRYSIN) IN API DRUGS - Sesharao, Maddi; Madhavarao, Vallabaneni (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Â Objective: The scope of the present work is a reversed-phase high-performance liquid chromatography (RP-HPLC) assay method developed for the simultaneous determination of baicalein and Chrysin in API drugs. Methods: The RP-HPLC method employed a Hypersil BDS C18 reversed-phase column (150Ã—4.6 mmÃ—5.0 Î¼m) with an isocratic mixture of water and acetonitrile in the ratio of 55:45; v/v as the mobile phase. The column temperature was kept at 25Â°C. The flow rate was 1.0 mL/min, and detection was by means of a photodiode array detector at wavelength of 268 nm and validated for various parameters such as specificity, system suitability, method precision, linearity, accuracy, solution stability, ruggedness, and robustness. Results: The system suitability parameters were evaluated from standard chromatograms by calculating the % relative standard deviation (RSD) from six replicate injections for baicalein and Chrysin peak areas. The % RSD for the peak area of the principal peak from six replicate injections of each standard solution was <2.0%. The linearity and correlation coefficient of baicalein and Chrysin was found to be 0.999. Method precision was performed, and % RSD from six different preparations for baicalein and Chrysin were found to be <2.0. The % recovery for each level was found to be the range of 98.0â€“102%. In ruggedness and robustness, the % RSD of the peak area of all peaks for six replicate injections should be not more than 2.0. Conclusion: Hence, the chromatographic assay method developed for baicalein and chrysin is said to be rapid, simple, specific, sensitive, precise, accurate, and reliable that can be effectively applied for routine analysis in research institutions, quality control department in industries, approved testing laboratories, bio-pharmaceutics, and bio-equivalence studies and in clinical pharmacokinetic studies.